Показники якості лакування відбитків цифровими технологіями репродукування - Сушко, Д. Р.; Скиба, В. М. (ТОВ «Видавництво Ліра-К», 2025)
This study explores the primary quality indicators relevant to digital varnishing, including gloss level, layer thickness uniformity, color shift (ΔE), drop volume consistency, and surface defects such as banding, bubbles, overspray, and missing spots. Several recent studies highlight that adhesion and surface tension are critical for achieving consistent layer formation, avoiding defects, and ensuring the required quality of color reproduction.
Keywords: репродукування; оздоблення цифрової упаковки